Issuers’ Insight for Identifying Choice of Sukuk Structuring - Datien Eriska Utami; Zulfa Irawati (University of Merdeka Malang, 2018)
One of the common problems that occur in Indonesia concerning the issuance of Sukuk is the limited issuance of Sukuk by companies. There were only two types of Sukuk issuance issued by companies, namely Mudaraba Sukuk and Ijarah Sukuk, and based on the data of OJK Sukuk Statistics, as of 2017 the issuance of Ijarah Sukuk still dominates Sukuk issuance. We investigated to discover how issuers of Sharia bonds (Sukuk) choose between the issuance of Mudaraba Sukuk and Ijarah Sukuk structures, based on the determinant factors of company characteristics, variables related to Sharia, and type of company industry. The population in this study were companies that issue Mudaraba Sukuk and Ijarah Sukuk. The sampling technique used is purposive sampling. The selection of the research sample consists of 27 issuers that issued 59 Ijarah Sukuk and 31 Mudaraba Sukuk during the period of observation. By implementing a probit regression analysis, the results showed that leverage level, Sharia compliance, and financial industry type might all influence the choice of companies to issue Mudaraba Sukuk.JEL Classification: G12, G23, O16DOI: https://doi.org/10.26905/jkdp.v22i4.2368